2017
DOI: 10.1590/0100-69912017005003
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and overall survival of breast cancer in the city of Goiania, Brazil: a population-based study

Abstract: Objective: to analyze the overall survival and prognostic factors of women with breast cancer in the city of Goiânia. Methods: this is a retrospective, cross-sectional, observational study that included women with malignant neoplasms of the breast identified by the Goiânia Population-based Cancer Registry. The variables studied were age at diagnosis, tumor size, staging, axillary lymph node involvement, tumor grade, disease extent, hormone receptors, and c-erb-B2 oncoprotein. We performed overall survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Cancer statistics can reveal the effectiveness of public health policies, the equity of resource distribution, and the impact of predictive factors on survival. Therefore, assessing breast cancer survival can help establish criteria for the objective evaluation of patient prognosis and can contribute to the improvement of cancer control strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer statistics can reveal the effectiveness of public health policies, the equity of resource distribution, and the impact of predictive factors on survival. Therefore, assessing breast cancer survival can help establish criteria for the objective evaluation of patient prognosis and can contribute to the improvement of cancer control strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized clinical trials conducted between the 1960s and the 1990s have reported a reduction in mortality from breast cancer of up to 40% in the female population of 50–69 years of age submitted to breast cancer screening [13]. In geographical regions with limited financial resources and difficulties in accessing standard oncological treatment [46], this strategy may represent an opportunity for more conservative treatments and better clinical outcomes [79].…”
Section: Introductionmentioning
confidence: 99%
“…Although metastatic breast cancer was not included as a separated health state, an additional decrease of utilities due to metastasis was reflected in a proportion (i.e. 8.4%) of patients within the breast cancer state [33]. Similarly, lower utility values due to end-stage ovarian cancer were applied to the proportion of women in the 'ovarian cancer' state, whose survival was expected to be < 1 year (i.e.…”
Section: Utilitiesmentioning
confidence: 99%